Successful Use of Intravenous Methylnaltrexone for Opioid-Induced Constipation in Critically Ill Pediatric Patients - Mills, Kimberly P.; McPherson, Christopher C.; Said, Ahmed S.; Lahart, Michael A. (Journal of Pediatric Intensive Care, 2021)
Objectives Methylnaltrexone is U.S. Food and Drug Administration (FDA) approved as a subcutaneous injection for adults with opioid-induced constipation (OIC). Case series have described the use of methylnaltrexone for OIC in the pediatric oncology population. There are limited data describing its intravenous use in critically ill pediatric patients.Methods We conducted a retrospective observational study at St. Louis Children's Hospital. Patients less than 18 years old who received at least one dose of intravenous methylnaltrexone while admitted to an intensive care unit between January 2016 and August 2019 were included. The primary outcome was documented laxation within 24 hours of methylnaltrexone administration.Results Sixteen patients received a total of 34 doses of intravenous methylnaltrexone. Patients received a median of 1.69 (interquartile range [IQR], 0.9–4.86) morphine milligram equivalents per kilogram per 24 hours, over a median of 14 days (IQR, 11–30), before methylnaltrexone administration. The median dose of methylnaltrexone was 0.15 mg/kg (IQR, 0.15–0.16). Ten patients (63%) responded to the first dose of methylnaltrexone, and 14 patients (88%) responded to at least one dose. Overall, 26 doses (76%) led to patient response. Four patients (25%) experienced adverse events (emesis, abdominal pain) after methylnaltrexone administration. No signs or symptoms of opioid withdrawal were documented.Conclusions Intravenous methylnaltrexone appears to be safe and effective in treating OIC in critically ill pediatric patients. No serious adverse events or signs of opioid withdrawal were observed after single and repeat dosing. Patients responded to methylnaltrexone with varying opioid dosing and durations prior to administration.
Keywords: methylnaltrexone; opioid-induced constipation; intensive care unit; pediatric; Peripherally acting mu-opioid receptor antagonists